The art of coding : the language of drawing, graphics, and animation - Al-Rifaie, Mohammad Majid; Ursyn, Anna, 1955-; Wyeld, Theodor G. (Chapman & Hall/CRC, 2020)
As the title suggests, this book explores the concepts of drawing, graphics and animation in the context of coding. In this endeavour, in addition to initiating the process with some historical perspectives on programming languages, it prides itself by presenting complex concepts in an easy-to-understand fashion for students, artists, hobbyists as well as those interested in computer science, computer graphics, digital media, or interdisciplinary studies. Being able to code requires abstract thinking, mathematics skills, spatial ability, logical thinking, imagination, and creativity. All these abilities can be acquired with practice, and can be mastered by practical exposure to art, music, and literature. This book discusses art, poetry and other forms of writing while pondering difficult concepts in programming; it looks at how we use our senses in the process of learning computing and programming. Features: Introduces coding in a visual way Explores the elegance behind coding and the outcome Includes types of outcomes and options for coding Covers the transition from front-of-classroom instruction to the use of online-streamed video tutorials Encourages abstract and cognitive thinking, as well as creativity The Art of Coding contains a collection of learning projects for students, instructors and teachers to select specific themes from. Problems and projects are aimed at making the learning process entertaining, while also involving social exchange and sharing. This process allows for programming to become interdisciplinary, enabling projects to be co-developed by specialists from different backgrounds, enriching the value of coding and what it can achieve. The authors of this book hail from three different continents, and have several decades of combined experience in academia, education, science and visual arts.